An Analysis of Television Satire on Kiky Saputri’s Roasting in Lapor Pak! - Kinasih, Putri Rindu; Marsella, Elisabeth (ppjbsip, 2023)
Humor has always been and will remain to be part of the political landscape, even though it may take a temporary break from time to time. The range of political humor is immense, including roasting comedy. In general, past research has succeeded in showing the importance of roasting comedy and how it employs the figure of speech. The problem is although the roasting is broadcast on national television, none of them has examined it using the theory of television satire. Thus, this research aimed to analyze the presupposition of roasting comedy and to study the roasting comedy by using the heuristic structures of television satire, which include: space, target, rhetoric, media, and time. The writers used qualitative methods to analyze the data using critical discourse analysis (CDA). This study used Kiky Saputri’s roasting video of DKI Jakarta governor Anies Baswedan in Lapor Pak! comedy program. The video was taken from the YouTube account Trans7 Official entitled “Kiky ROASTING Anies Baswedan, Pasukan Auto Jantungan! | LAPOR PAK! (09/11/21) Part 4”. This program was selected for its popularity and has won the Indonesian Television Award (ITA) 2021 in the most popular non-drama primetime program category. Among the program's episodes, this episode has become viral with more than 6.8 million views and was widely published in major national news portals. From the analysis, it can be concluded that Kiky Saputri’s roasting comedy has a specific pattern. Furthermore, because the Lapor Pak! program fulfilled Jones' heuristic structure, Kiky Saputri's roasting Anies Baswedan attracted much attention.